Penerapan Gaya Kepemimpinan Situasional oleh Kepala Sekolah di SMPN 2 Sampanahan - Abdul Majid; Suparmi Suparmi; Tri Hartini; Aslamiah Aslamiah; Celia Cinantya (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2025)
This study aims to examine the application of situational leadership theory by the principal of SMP Negeri 2 Sampanahan, Kotabaru Regency, and its impact on organizational behavior within the school environment. A qualitative approach with a case study method was employed, involving in-depth interviews with the principal, teachers, and students. The main focus of the research is to understand how the principal adapts leadership styles according to the needs and conditions of the individuals being led. The findings reveal that the principal successfully applied various leadership styles—ranging from directive, supportive, participative, to delegative—flexibly based on the specific situations encountered. This adaptability positively influenced the organizational climate, fostered harmonious working relationships, and enhanced the motivation and active participation of both teachers and students. The school environment became more conducive and collaborative, ultimately leading to overall performance improvement. These findings highlight the importance of adaptive leadership in education to support the achievement of organizational goals and the development of human resources within schools. This study contributes to the development of leadership practices in educational settings, particularly in the context of educational management that is responsive to both internal and external institutional dynamics.